2013
DOI: 10.1155/2013/241830
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behaviour of Ti-6Al-4V Alloy with Nitride Coatings in Simulated Body Fluids at 36C and 40

Abstract: Nitride coatings were formed on Ti-6Al-4V alloy by thermodiffusion treatment. The corrosion-electrochemical behaviour of Ti-6Al-4V alloy with nitride coatings I and II was investigated in physiological solutions (0.9% NaCl and Tyrode's) at temperatures of 36∘C and 40∘C. It is determined that nitride coating I provides Ti-6Al-4V alloy the higher corrosion resistance in Tyrode's solution at both temperatures of solution while nitride coating II in isotonic 0.9% NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
2
Order By: Relevance
“…Pohrelyuk et al (2013) demonstrated, for nitride Ti6Al4V alloys, that I corr ( μ A/cm 2 ) of both thin and thick films varied from 6 to 15, respectively, when 0.9 percent NaCl was used at 36°C. Recent studies have shown that grain size is a critical factor in the corrosion resistance of metallic materials and mechanical properties (Unal et al , 2014; Mao et al , 2011; Wang, Yu and Dong, 2006), where smaller grain size is associated with better corrosion resistance.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Pohrelyuk et al (2013) demonstrated, for nitride Ti6Al4V alloys, that I corr ( μ A/cm 2 ) of both thin and thick films varied from 6 to 15, respectively, when 0.9 percent NaCl was used at 36°C. Recent studies have shown that grain size is a critical factor in the corrosion resistance of metallic materials and mechanical properties (Unal et al , 2014; Mao et al , 2011; Wang, Yu and Dong, 2006), where smaller grain size is associated with better corrosion resistance.…”
Section: Resultsmentioning
confidence: 97%
“…Most applications of titanium involve mixing it with small amounts of aluminum and vanadium, typically 6 and 4 percent, respectively, by weight, to form a metallic alloy, which is normally indicated as Ti6Al4V. The nitriding of this ternary titanium alloy (TiAlVN) enables enhanced mechanical properties, high resistance to corrosion and wear and good hardness and tenacity (Pohrelyuk et al , 2013). Few studies have been applied on this alloy as thin film; for instance, in previous work, we have demonstrated a successful preparation of TiAlV films by vacuum arc discharge technique starting from Ti, Al and V elemental targets (Abdallah, Mrad and Ismail, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Os efeitos da temperatura, tempo e atmosfera do gás sobre a nitretação por plasma da liga Ti-6Al-4V são complexos. O nitrogênio puro, uma mistura de nitrogênio e hidrogênio, uma mistura de nitrogênio e argônio e uma mistura de todos os três gases em várias proporções têm sido utilizados como atmosfera para a nitretação por plasma (RAAIF et al, 2007;RAHMAN et al, 2007;LIMA, 2010;HOSSEINI;AHMADI, 2013;POHRELYUK;TKACHUK;PROSKURNYAK, 2013;TANG et al, 2013). As funções da adição do hidrogênio no plasma é a de capturar os átomos de oxigênio presentes na atmosfera reduzindo as impurezas (MICHEL; CZERWIEC; GANTOIS, 1995) e também porque a presença do hidrogênio diminui a energia necessária para a produção de átomos de nitrogênio via dissociação molecular por colisão, já que os íons de H + , que têm menor massa e maior energia cinética do que os íons N + nas mesmas condições de pressão, tensão e temperatura, podem se dissociar em moléculas N 2 e espécies de NH x através da colisão em energias mais baixas para produzir átomos de nitrogênio ativos (BINGZHONG; YINGZHI, 1987).…”
Section: Parâmetros Do Processo De Nitretaçãounclassified
“…A liga de Ti-6Al-4V nitretada por plasma apresenta maior dureza superficial e tensão residual compressiva mais elevada em comparação com o material não nitretado, o que segundo vários autores (FU et al, 1998;GOLDEN et al, 2007 2004).…”
Section: Nitreto De Titâniounclassified